The Effects of Family/Community and School Discourses on Children's and Adolescents' Interpretations of United States History. Issue 1 (1st January 2006) - Epstein, Terrie
Abstract : In the post 9/11 era the Al Queda factor is a major influence in shaping the Historical, Humanities, Social Sciences and Citizenship curriculum. Central is the issue of racial identity and the ability of school teachers to engage pupils in discourses that recognise both diversity and the need to understand the beliefs, values and mores of different ethnic groups. A central concern are the master narratives of such ethnicities, modified and individualized through the filters of family, culture and community. The paper indicates that unless teachers take into account the dominant role which family and community play in shaping the historically defined identities of students then stereotypes will neither be challenged nor changed. Through a detailed longitudinal study of students in six classes the research identified the problem that a transmission, didactic pattern of pedagogy is unable to modify student values, beliefs and attitudes. It recommends a model of teaching that is interactive, discursive and empowers students to discuss, debate and analyse identity from the perspective of ethnicities different from their own. A shift to a constructivist pedagogy will empower students to create their own historicised identities that understand and allow for the perspectives of other ethnicities.